Urbanization-induced geo-environmental changes in Naogaon municipality, Bangladesh: a comprehensive assessment - Md. Abdur Rahman,; Bokul Kumar Ghose, (International Journal of Advanced Geosciences, 2024)
This study examines how urban growth impacts the environment in Naogaon Municipality, Bangladesh. We analyzed changes in land use, soil quality, water resources, air quality, and more. Our findings show that urbanization leads to loss of green spaces and agricultural lands, affecting biodiversity and soil fertility. Industrial activities and traffic contribute to air and water pollution. Drainage systems are extensive but unevenly distributed, and waste management needs improvement. We recommend comprehensive strategies to address these environmental challenges for sustainable urban development.